Matter That Embodies: Agentive Flesh and Working Bodies/Selves. Issue 5 (May 2022) - Harding, Nancy; Gilmore, Sarah; Ford, Jackie
The post-Cartesian 'material turn' in management and organization studies understands that bodies are far more than vehicles that enable work to be undertaken, but are agentive actors in the constitution of work and working selves. This leads to the need for more empirically derived understanding of the agency of flesh in the performative corporealization of working, embodied selves. We met this challenge through adapting feminist, posthuman research methods for a study of the materialities and materialization of working bodies. The study takes forward Judith Butler's and Karen Barad's theories of performativity by reading them through each other, and introducing flesh as an agentive actor in each moment-to-moment move. In paying close attention to the speech of supposedly 'dumb flesh' we show how flesh resists its negation and itself imposes control on the worker. We coin the term 'body/flesh' and illuminate how bodies are active and agentive, constituting corporeal/izing working selves in somewhat unexpected ways.